The solution of the provided equation (x – 3)(x 9), which is the product of two binomial equation, is 0.
The solution of the quadratic equation is the solution of the variable of the equation, for which the equation satisfies.
To find the solution of the equation, equate it to zero after factorizing it.
The equation provided in the problem is,
[tex](x - 3)(x+ 9)=-27[/tex]
Simplify the equation with the help of mathematical operations,
[tex](x - 3)(x+ 9)=-27\\x^2-3x+9x-27=-27\\x^2+6x-27+27\\x^2+6x=0\\x(x+6)=0[/tex]
Equate the factors to zero,
[tex]x=0;\; x=-6[/tex]
Hence, the solution of the provided equation (x – 3)(x 9), which is the product of two binomial equation, is 0.
Learn more about the solution of the equation here;
https://brainly.com/question/21283540